Cord blood leptin and insulin-like growth factor levels are independent predictors of fetal growth - Papathanassoglou, Elizabeth; Christou, Helen; Connors, Jean Marie (My University, 2001)
The insulin-like growth factor (IGF) system is the dominant endocrine regulator of fetal growth, whereas insulin has a permissive role. Although a role for leptin in fetal growth has been suggested recently, the mechanism by which leptin may be related to fetal growth is not known; but leptin may interact with the IGF system in utero as it does in the extrauterine life. In the context of a hospital-based case control study, we collected anthropometric and demographic data and measured serum leptin, IGF-I, IGF-II, insulin, cortisol, and IGF binding protein 3 concentrations in 142 cord blood samples from full-term deliveries. Cord leptin, IGF-I, and insulin levels correlated positively with birth weight (r = 0.46, r = 0.41, and r = 0.21, respectively, P < 0.01) by univariate analysis and were significantly higher in large-for-gestational-age (LGA) infants, compared with appropriate-for-gestational-age (AGA) infants. Cord leptin concentrations correlated with insulin levels (r = 0.36, P<0.01) but not with IGF-I levels (r = 0.20). Multiple linear and logistic regression analysis demonstrated an independent positive relationship of both leptin and IGF-I with birth weight and AGA/LGA status. The positive association of leptin levels with birth weight and AGA/LGA status cannot be attributed to IGF-I. This suggests the existence of alternative mechanisms underlying leptin's associations with fetal growth that should be further explored
Keywords: Endocrinology; Metabolism; Insulin; Leptin; Fetus--Development; Hydrocortisone; Birth weight